A versatile, efficient strategy for assembly of multi-fragment expression vectors in Saccharomyces cerevisiae using 60 bp synthetic recombination sequences - Kuijpers, Niels GA (BioMed Central, 2013)
BACKGROUND: In vivo recombination of overlapping DNA fragments for assembly of large DNA constructs in the yeast Saccharomyces cerevisiae holds great potential for pathway engineering on a small laboratory scale as well as for automated high-throughput strain construction. However, the current in vivo assembly methods are not consistent with respect to yields of correctly assembled constructs and standardization of parts required for routine laboratory implementation has not been explored. Here, we present and evaluate an optimized and robust method for in vivo assembly of plasmids from overlapping DNA fragments in S. cerevisiae. RESULTS: To minimize occurrence of misassembled plasmids and increase the versatility of the assembly platform, two main improvements were introduced; i) the essential elements of the vector backbone (yeast episome and selection marker) were disconnected and ii) standardized 60 bp synthetic recombination sequences non-homologous with the yeast genome were introduced at each flank of the assembly fragments. These modifications led to a 100 fold decrease in false positive transformants originating from the backbone as compared to previous methods. Implementation of the 60 bp synthetic recombination sequences enabled high flexibility in the design of complex expression constructs and allowed for fast and easy construction of all assembly fragments by PCR. The functionality of the method was demonstrated by the assembly of a 21 kb plasmid out of nine overlapping fragments carrying six glycolytic genes with a correct assembly yield of 95%. The assembled plasmid was shown to be a high fidelity replica of the in silico design and all glycolytic genes carried by the plasmid were proven to be functional. CONCLUSION: The presented method delivers a substantial improvement for assembly of multi-fragment expression vectors in S. cerevisiae. Not only does it improve the efficiency of in vivo assembly, but it also offers a versatile platform for easy and rapid design and assembly of synthetic constructs. The presented method is therefore ideally suited for the construction of complex pathways and for high throughput strain construction programs for metabolic engineering purposes. In addition its robustness and ease of use facilitate the construction of any plasmid carrying two or more genes.